Stress Evolution in Punch-Through Shear Tests: A Numerical Study Based on Discrete Element Method - Liu, Jie; Wan, Wen; Zhao, Yanlin; Fan, Xiang (Frontiers in Physics, 2020)
The discrete element method is adopted to investigate the dynamic failure process in punch-through shear tests. The numerical tests agree well with the laboratory tests on crack propagation sequence and the influence of confining stress on shear fracture toughness. More importantly, the numerical tests indicate that the increase in axial force first causes stress concentrations. When the stresses reaches critical values, cracks initiate and the concentrated stresses dissipate. With further increase in axial displacement, the axial force may fluctuate, accompanying with crack development. In addition, the increase in confining stress promotes the critical values of the concentrated stresses before crack propagation. Thus, the numerical tests verifies the previous statements that the increase in confining stress promotes the shear fracture toughness and restrains the propagation of tensile cracks.